2020
DOI: 10.13106/jafeb.2020.vol7.no8.233
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Board Chairmen in Audit Committees and Earnings Management: Evidence from Malaysia

Abstract: This paper investigates the effect of the involvement of the board chairman in the audit committee (AC) on earnings management (EM). It examines Bursa Malaysia-listed companies with the lowest positive earnings for the years 2013 to 2015. The Modified Jones Model by Kasznik (1999) was used to determine discretionary accruals. An AC that includes its board chairman as an ordinary member is associated with greater discretionary accruals. However, a board chairman who is also the chairman of the AC does not seem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
(78 reference statements)
0
16
0
Order By: Relevance
“…The findings of the current study are supported through the organizational theory and contingency theory. The organizational theory discusses that control strategy is an important factor that affects the company's performance and it mentions that the higher control level on the managers' behavior and outcome, will improve the company's performance (Al-Absy et al, 2020;Upadhaya et al, 2014;Jones, 1995). As well, the contingency framework discusses that managerial practices or behavior and managerial human capital as production factors affect the company's performance (Bloom & Reenen, 2007;Ichniowski et al, 1997;Lucas, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the current study are supported through the organizational theory and contingency theory. The organizational theory discusses that control strategy is an important factor that affects the company's performance and it mentions that the higher control level on the managers' behavior and outcome, will improve the company's performance (Al-Absy et al, 2020;Upadhaya et al, 2014;Jones, 1995). As well, the contingency framework discusses that managerial practices or behavior and managerial human capital as production factors affect the company's performance (Bloom & Reenen, 2007;Ichniowski et al, 1997;Lucas, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Many aspects contribute to enhancing the efficiency of internal auditing, some of which are linked to auditors, such as independence and objectivity, and some are related to senior management, such as providing the necessary support for auditing management so that the work can be carried effectively (Dellai & Omri, 2016). The independence of members of audit committees is positively related to the quality of profits in institutions and companies, and therefore heads of boards of departments should not be involved as members of audit committees because of its negative impact on performance and quality of profits (Al-Absy et al, 2020). If the internal auditors followed the standards that regulate the profession of IA which will leads to contribute positively to improving and regularizing performance (Getie Mihret et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Saona et al (2019) indicated that there is a significant negative relationship between insiders' ownership, the controlling shareholder, and earnings manipulation; in this case, high insider ownership and a majority controlling shareholder support the governance system, which contributes to improving the independency level in an organization. The greater proportion of independent directors oversees managers more efficiently, and therefore earnings manipulation will be decreased (Al-Absy et al, 2020;Huynh, 2020). Ding et al (2007) confirmed that the relationship between ownership concentration and earnings manipulation is an inverted U-shape.…”
Section: Introductionmentioning
confidence: 70%